KAJIAN HADITS PERSPEKTIF ORIENTALIS - Sholihah, Izzatus (SAMAWAT: Journal Of Hadith and Qur’anic Studies, 2022)
For Orientalists, almost all studies of Islam become interesting things. Although initially Orientalist studies were aimed at problems in the fields of literature and history. Furthermore, they directed their studies to the Islamic sciences, especially to the field of the Prophet's hadith. This is understandable, because the hadith of the Prophet SAW is one of the sources of Islamic teachings. So if you want to study Islamic issues, it cannot be separated from the study of the hadith of the Prophet SAW. The studies conducted by the Orientalists on the Islamic sciences, especially on the Hadith of the Prophet SAW, have led to pro and contra attitudes among Muslim scholars and scholars internally. Some see it as positive and some see it as negative. Indeed, in this study there are several weaknesses due to their subjectivity towards Islamic studies, but some are considered meritorious and have a great contribution, especially in maintaining and developing the study of the Prophet's hadith. In this simple article, the author will discuss a little about the progress of the Orientalists in studying the traditions of the Prophet Muhammad, starting from the meaning and history of the emergence of Orientalism, mapping in the study of hadith, methodological criticism and their contribution to the study of hadith. Kata Kunci: Orientalist, Hadith.